The Clinicopathological and Prognostic Significance of SOX9 Expression in Gastric Cancer: Meta-Analysis and TCGA Analysis - Zu, Guo; Gao, Jiacheng; Zhou, Tingting (Frontiers in Oncology, 2021)
Background: The clinicopathological and prognostic significance of SOX9 expression in gastric cancer (GC) patients are still controversial. Our aim is to investigate the clinicopathological and prognostic value of SOX9 expression in GC patients. Methods: A systemic literature search and meta-analysis was used to evaluate the clinicopathological significance and overall survival (OS) of SOX9 expression in GC patients. TCGA dataset was used to investigate the relationship between SOX9 expression and OS of stomach adenocarcinoma (STAD) patients. Results: A total of 11 articles involving 3,060 GC patients were included. In GC patients, the SOX9 expression was not associated with age (OR=0.743, 95%CI=0.507-1.089, P=0.128), sex (OR=0.794, 95%CI=0.605-1.042, P=0.097), differentiation (OR=0.728, 95%CI=0.475-1.115, P=0.144) and lymph node metastasis (OR=1.031, 95%CI=0.793-1.340, P=0.820). SOX9 expression was associated with depth of invasion (OR=0.348, 95%CI=0.247-0.489, P=0.000) and TNM stage (OR=0.428, 95%CI= 0.308-0.595, P=0.000). The 1-year OS (OR=1.507, 95%CI= 1.167-1.945, P=0.002), 3-year OS (OR=1.482, 95%CI=1.189-1.847, P=0.000) and 5-year OS (OR=1.487, 95%CI= 1.187-1.862, P=0.001) were significantly shorter in GC patients with high SOX9 expression. The TCGA analysis showed that SOX9 was up-regulated in STAD patients compared with normal patients (P < 0.001), and the OS of STAD patients with high-expression of SOX9 is poorer than the patients with low-expression of SOX9, but the statistical difference is not obvious (P=0.31). Conclusion: SOX9 expression was associated with depth of tumor invasion, TNM stage and poor OS of GC patients. SOX9 may be a potential prognostic factor for GC patients, but needs to further study.